Arguing in Front of the Children - Diana Converse (EDIS)
FAR-0073, a 2-page transcript of the Family Album Radio Program broadcast by Diana Converse, provides research-based advice for parents about whether and how parents should handle arguments in front of their children. Includes references. Published by the UF Department of Family Youth and Community Sciences, March 2009.